STUDENTS’ OPINION ON NON-ENGLISH SUBJECTS TAUGHT IN UNIVERSITY: A DESCRIPTIVE RESEARCH - Rafi Aryasutha; Rizky Surya Ramadhan; Muhammad Khoirul Anwar; Lestari Budianto (PROJECT (Professional Journal of English Education), 2024)
There is constant discussion in the English department regarding the study of non-English courses. The purpose of this study is to find out what the students think about taking non-English courses in the English department. This research used a descriptive qualitative research method involving 9 participants who were first-semester students in the English department at K.H. University. Abdul Chalim. The results of this research reveal that there are two parties, namely supporting and rejecting. Each party has its reasons. However, this research is limited in the variety of research participants. Therefore, it is recommended that future research be able to conduct similar research by increasing the variety of participants.